2022
DOI: 10.1109/access.2022.3199411
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Dynamic Gesture Recognition Using MmWave Radar

Abstract: Millimeter-wave (mmWave) radar sensors are a promising modality for gesture recognition as they can overcome several limitations of optic sensors typically used for gesture recognition. These limitations include cost, battery consumption, and privacy concerns. This work focuses on finger level (called micro) gesture recognition using mmWave radar. We propose a set of 6 micro-gestures that are not only intuitive and easy to perform for the user but are distinguishable based on Doppler and angle variation in tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The average rate falls inside the moderate category (<.3) [76]. There are no referents with a very high rate of agreement, 1 19 =5% has a high agreement, 17 19 =90% has a moderate agreement, and 1 19 =5% receive a low agreement. The referents in this study are not linked to any environment or device, such as a smart home, smartphone, or smart car, therefore participants were not so subject to the legacy bias [77], which also explains the low magnitudes as they were unfamiliar with these functions.…”
Section: ) Agreement Ratementioning
confidence: 94%
See 1 more Smart Citation
“…The average rate falls inside the moderate category (<.3) [76]. There are no referents with a very high rate of agreement, 1 19 =5% has a high agreement, 17 19 =90% has a moderate agreement, and 1 19 =5% receive a low agreement. The referents in this study are not linked to any environment or device, such as a smart home, smartphone, or smart car, therefore participants were not so subject to the legacy bias [77], which also explains the low magnitudes as they were unfamiliar with these functions.…”
Section: ) Agreement Ratementioning
confidence: 94%
“…On one hand, radar-based gesture recognition systems have demonstrated their effectiveness [10], reliability, and robustness [11] despite being influenced by environmental conditions [12]. Most studies [12]- [18] have reported their perfor-mance in terms of high recognition accuracy rates, making dynamic [16], [17], real-time [19]- [21] interaction feasible. High-frequency, wide-bandwidth radars detect even the finest movements [22], such as the fingers of a hand [23], at a reasonable distance [24].…”
Section: Introductionmentioning
confidence: 99%
“…Operating between 58 -60 GHz with one transmitter and three receiver antennas, the radar was used to detect and classify macro hand-gestures with a vocabulary size of three: sweep left-to-right, sweep right-toleft, and hand-tap. As is common in frame-based radar processing, we used the Time-Velocity Diagram (TVD) and Time-Angle Diagram (TAD) as described in [4], computed from the radar CIR signal, as input features to an ML classifier to classify the gesture. Additionally, a ML-based activity detection module was used to segment the gestures.…”
Section: Synthesis Of Radar Cir and Computation Of Featuresmentioning
confidence: 99%